2019
DOI: 10.4102/phcfm.v11i1.1994
|View full text |Cite
|
Sign up to set email alerts
|

Rural Zulu women’s knowledge of and attitudes towards Pap smears and adherence to cervical screening

Abstract: BackgroundCervical cancer is the most common form of cancer in black women in South Africa and has almost a 60% mortality rate. However, adherence to cervical screening programmes of black women living in rural South Africa is not universal.AimThe aim of this study was to gain a better understanding of rural Zulu women’s knowledge of and attitudes towards Pap smear tests, and their reasons for participation or non-compliance with cervical screening.SettingThis study was conducted at the gynaecology and antenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Poor knowledge of disease detection and prevention has often been linked to high prevalence and late diagnosis of cervical cancer, but evidence about interventions that effectively addresses this problem is limited 25. Consistent with previous reports, the present study confirmed that South African women lack this basic knowledge 26 27. Importantly, in this report simple health education during a vaccine implementation project had a measurable and significant positive effect on the knowledge of mothers of primary school children.…”
Section: Discussionsupporting
confidence: 90%
“…Poor knowledge of disease detection and prevention has often been linked to high prevalence and late diagnosis of cervical cancer, but evidence about interventions that effectively addresses this problem is limited 25. Consistent with previous reports, the present study confirmed that South African women lack this basic knowledge 26 27. Importantly, in this report simple health education during a vaccine implementation project had a measurable and significant positive effect on the knowledge of mothers of primary school children.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, 40% of Black women reported ever having done a Pap smear compared to 91% White, 83% Coloured and 78% of Asian women [26]. The barriers to CC screening in black women in South Africa include lower socioeconomic position, lack of knowledge on CC screening, cultural beliefs as well as fear and stigma [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of knowledge about cervical cancer has also been reported in other studies within the province of KwaZulu-Natal (KZN) as well as other provinces in South Africa and elsewhere in Africa. 16,18,19,29,[40][41][42][43] Women have previously expressed the need for female targeted education, screening centres and support groups. 29 Participants in this study also stressed the importance of the community both in terms of education and support.…”
Section: Discussionmentioning
confidence: 99%